Biological Aspects of Reproduction Natural Betta Fish (Betta imbellis) in the General Fisheries Faculty of Fisheries and Maritime Affairs, University of Riau - Dedi Purnomo; Windarti Windarti; Deni Efizon (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTBetta imbellis is a small ornamental fish and they areinhabit the  Fisheries and Marine Science Faculty, Riau University. A study aims to understand the reproductive biologi of B. imbellishas been conducted from February-April 2019. Fish sampling were conducted 2 times/week. Parameters measured were sex ratio, gonad maturnity level, gonad somatic indexs (GSI), fecundity, and egg diameter. Total fish captured was 110 (39 males and 71 fermales). Sex ratio between male and fermale  was 1:2. There were  differences between male and fermale, there  was black pointed area in the body of male fish. The  male genital papila was elongated, while that of the female was   rounded. Male and female fishes in 1th, 2nd and 4th maturity levels were found.   The GSI of females ranged from 4.15-24.00% and while that of the males was 6.04-35.09%. The fecundity of the fish ranged from 52-72 eggs/fish and the fish was categorized as a total spawner. Keywords:     The black ponted area, Sex ratio, gonad maturity level, gonad somatic index, fecundity, total spawner